Worse health status, sleeping problems, and anxiety in 16-year-old students are associated with chronic musculoskeletal pain at three-year follow-up - Julia S. Malmborg; Ann Bremander; M. Charlotte Olsson; Anna-Carin Bergman; A. Sofia Brorsson; Stefan Bergman (BMC, 2019)
Abstract Background Chronic musculoskeletal pain is common in adolescents, and it has been shown that adolescents with pain may become young adults with pain. Pain often coincides with psychosomatic symptoms in adults, but little is known about longitudinal associations and predictors of pain in adolescents. The aim was to investigate chronic musculoskeletal pain and its associations with health status, sleeping problems, stress, anxiety, depression, and physical activity in 16-year-old students at baseline, and to identify risk factors using a three-year follow-up. Methods This was a longitudinal study of 256 students attending a Swedish upper secondary school. Questionnaires regarding chronic musculoskeletal pain and distribution of pain (mannequin), health status (EQ-5D-3 L), sleeping problems (Uppsala Sleep Inventory), stress symptoms (single-item question), anxiety and depression (Hospital Anxiety and Depression Scale), and physical activity (International Physical Activity Questionnaire) were issued at baseline and follow-up. Student's t-test and chi2 test were used for descriptive statistics and logistic regression analyses were used to study associations between chronic pain and independent variables. Results Fifty-two out of 221 students at baseline (23.5%) and 39 out of 154 students at follow-up (25.3%) were categorized as having chronic musculoskeletal pain. Chronic musculoskeletal pain at follow-up was separately associated with reporting of an EQ-5D value below median (OR 4.06, 95% CI 1.83-9.01), severe sleeping problems (OR 3.63, 95% CI 1.69-7.82), and possible anxiety (OR 4.19, 95% CI 1.74-10.11) or probable anxiety (OR 3.82, 95% CI 1.17-12.48) at baseline. Similar results were found for associations between chronic musculoskeletal pain and independent variables at baseline. In multiple logistic regression analysis, chronic musculoskeletal pain at baseline was a predictor of chronic musculoskeletal pain at follow-up (OR 2.99, 95% CI 1.09-8.24, R2 = 0.240). Conclusion Chronic musculoskeletal pain at baseline was the most important predictor for reporting chronic musculoskeletal pain at the three-year follow-up, but a worse health status, severe sleeping problems, and anxiety also predicted persistence or development of chronic musculoskeletal pain over time. Interventions should be introduced early on by the school health services to promote student health.